The effects of high-intensity combined training program on cardiorespiratory function, isokinetic trunk strength and anaerobic power of canoe athletes - Jung, J. H. (Journal of the Korean Applied Science and Technology, 2020)
The purpose of this study is to confirm the effects of a 6-week high-intensity combined training program on canoe athletes' cardiorespiratory function, isokinetic trunk strength, and anaerobic power. For the purpose of this study, the high-intensity combined training program was applied to 9 high-school canoe athletes. The high-intensity combined training program consists of aerobic exercise performed 2 times a week (Tuesday and Thursday), anaerobic exercise performed 3 times a week (Monday, Wednesday, and Friday), and flexibility exercise performed 5 times a week. The core of the high-intensity combined training program was the anaerobic training program performed with 100% weight for repetition; otherwise, the existing training method was divided into the percentage (%) of the 1RM. The aerobic exercise and the gym ball exercise are performed subsidiarily. Results showed that there was a statistically significant difference in height and muscle mass, whereas there was no statistically significant difference in weight, body fat percentage, and BMI followed by the high-intensity combined training program. There were statistically significant differences in maximum oxygen uptake and total exercise time. The angular velocity of 30°/sec showed a statistically significant difference in the peak torque item of flexors only. Also, the angular velocity of 120°/sec showed a statistically significant difference in the total work item of extensors only; however, there was no statistically significant difference in all the items of peak power, average power, and peak drop. In conclusion, it seems that the high-intensity combined training program may be applied as a training program for enhancing canoe athletes' performance. For further studies, more than 6 weeks training program with more participants would show improved results of isokinetic strength and anaerobic power in athlets.